Uji Kemampuan Tumbuh Isolat Bakteri dari Air dan Sedimen Sungai Tallo Terhadap Logam Timbal (Pb) - Fahruddin Fahruddin; Nur Haedar Nur Haedar; Slamet Santoso; Sri Wahyuni (Jurnal Ilmu Alam dan Lingkungan, 2019)
The stretch of the Tallo River which stretches across the Makassar city area, and not far from the Makassar Industrial Area, causes contamination of various heavy metals. Some bacteria grow in the presence of toxic properties on heavy metals. The purpose of this study was to obtain bacterial isolates that were able to grow at several concentrations of lead (Pb).Bacteria were isolated by using Nutrient Agar has been added Pb (NO)3 10 ppm. Resistance test was conducted by turbidimetry using a spectrophotometer. Based on research that has been done, the result of isolation of resistant bacteria lead from Tallo River showed that 5 isolates from samples of sediment with code isolates SM3, SM5, SM6, SM9 and SM10, while for the water samples obtained 3 isolates by code isolates AR1, AR2 and AR3. Ability to resist bacteria ie until the concentration of 50 ppm, while the highest growth ability of each different isolates, the highest growth capability isolates SM3, SM6 SM10 and AR3 at a concentration of 10 ppm. SM5 isolates had the highest growth capability at a concentration of 15 ppm. AR2 isolates had the highest growth capability at a concentration of 20 ppm. Isolates SM9 and AR1 has the highest growth capability at a concentration of 25 ppm.